Odonata biodiversity of the Argentine Chaco biome - Von Ellenrieder, Natalia (2010)
Odonates of small temporary pools, marshes, large permanent ponds, oxbow lakes, dams, and perennial rivers were sampled in the semiarid Chaco biome of NW Argentina between September 2007 and December 2008. Information from 35 localities yielded 60 species; presence/absence information of species was recorded in a spatial-relational database. Alpha, beta, and gamma diversity and total species richness expected for the area were estimated, and structure of Chaco odonate assemblages was preliminarily analyzed using nonmetric multidimensional scaling (NMS) ordination. Species composition was found to be related to both habitat type and longitudinal sector. Some species that might be indicative of habitat type were identified. — In order to analyze the distribution and biogeography of the odonates of the Chaco biome in Argentina, collections and literature were also examined, adding 58 localities (93 total) and 28 species (88 total). Odonate diversity of the Chaco was compared with that of neighboring Yungas and Paranense biomes by means of percent complementarity and cluster analysis, which showed Chaco odonate composition to be slightly more similar to that of the Yungas than to the Paranense biome, and W and E Chaco sectors to be more similar between them than with either of the two neighboring biomes. Most odonate species found in the Chaco are vagile and more widely distributed in the Neotropical region, with only four potential endemics.